Synthesis, characterization and Biological activity of organotin (IV) complexes with hydrazine ligands - Irene, Foo Ping Ping (Universiti Malaysia Sarawak (UNIMAS), 2009)
This thesis report four new chelating hydrazone ligands containing ONO- and ONN-donor atoms and their organotin(IV) complexes. Research works have been focused on the synthesis, spectroscopic characterization, structural elucidation and biological activities studies of these hydrazone ligands and their organotin(IV) complexes. The four new chelating hydrazone ligands used were: pyruvic acid-4-hydroxybenzhydrazone [H3PAB] (1), methyl pyruvate-4-hydroxybenzhydrazone [H2MPB] (2), pyruvic acid-2- pyridylhydrazone [HPAP] (13) and benzoylacetone isonicotinylhydrazone [H2BAS] (20). New organotin(IV) complexes have also been derived from tly; se four mentioned hydrazone ligands with R,,, SfCl2_m [R = Me, nBu, tBu or Ph; m = I or 2] in the presence of base in absolute methanol using Schlenk vacuum line technique under dry N2-atmosphere. The analytical and physico-chemical techniques such as elemental analyses, UV-Visible, IR, and 'H NMR studies have been used for the characterization of hydrazone ligands (1-2, 13, 20) and their organotin(IV) complexes (3-12, 14-19, 21-26). Among them, molecular structures of [nBu2Sn(HPAB)] (4), [nBuSnC12(PAP)] (18) and [Me2Sn(BAS)] (21) have also been characterized by single crystal X-ray diffraction methods. Molar conductance values showed that all the organotin(IV) complexes (3-12, 14-19, 21-26) are non-electrolytes. New hydrazone ligands, [H3PAB] (1) and [H2MPB] (2) are reacted with organotin(IV) chloride(s) to torn [R2Sn(HPAB)] [R = Me (3), nBu (4), tBu (5) and Ph (6)], [RSnCI(HPAB)] [R = Me (7) and Ph (8)], [R2SnCI(HMPB)] [R = Me (9), nBu (10) and Ph (11)] and [MeSnC12(HMPB)] (12). The X-ray single crystal analysis data of [nBu2Sn(HPAB)] (4) confirmed that compound (4) is five-coordinated in a distorted trigonal-bipyramidal geometry configuration. [nBu2Sn(HPAB)] (4) is orthorhombic with space group C2/c. The ligand [H3PAB] (1) acts as a dinegative tridentate ligand coordinating via the carboxylic-O, imine-N and enolic-O atoms in the formation of [nBu2Sn(HPAB)] (4). From the elemental analyses and spectroscopic studies of ligand [H2MPB] (2) and its organotin(IV) complexes (9-12), [H2MPB] (2) is proposed to coordinate as a dinegative tridentate entity towards the central tin atom, coordinating through the carboxylate-O, the imine-N and enolic-O atoms to form organotin(IV) complexes (9-12). Another hydrazone ligand, [HPAP] (13) and its organotin(IV) complexes, [R2SnC1(PAP)] [R = Me (14), nBu (15) and Ph (16)] and [RSnC12(PAP)] [R = Me f 17), nBu (18) and Ph (19)] are also prepared and characterized. Single crystal X-ray data showed that [nBuSnCI2(PAP)] (18) has six coordination number in a distorted octahedral configuration. [HPAP] (13) acted as mononegative tridentate ligand which coordinated via carboxylic-O, imine-N and pyridyl-N atoms. The X-ray crystal structure proved that [nBuSnC12(PAP)] (18) is tetragonal with space group I4i/a. Reaction of [HZBAS] (20) with organotin(IV) chloride(s) produced [R2Sn(BAS)] [R = Me (21), nBu (22) and Ph (23)] and [RSnCI(BAS)] [R = Me (24), nBu (25) and Ph (26)]. X-ray crystallographic analysis revealed that [Me2Sn(BAS)] (21) is penta-coordinated and adopts a distorted trigonal-bipyramidal configuration via 0, N, 0-donor atoms from the [H2BAS] (20) which acted as dinegative tridentate ligand. The crystal structure of [Me2Sn(BAS)] (21) is monoclinic with space group P2(1)/n. he preliminary toxicity test revealed that all the organotin(IV) complexes (3-12, 14-19, 21-26) are more toxic against Artemia salina than the free hydrazone ligands [H2BAS] (1), [H2MPB] (2), [HPAP] (13) and [H2BAS] (20). In general, di-n-butyltin(IV) complexes (4, 10 and 15) were the most toxic with the lowest LC50 values for the hydrazone ligands [H3PAB] (1), [H2MPB] (2) and [HPAP] (13). The LC50 values for complex (4, 10 and 15) were 11.40, 26.07 and 13.24 μg/mL, respectively. However, in the series of ligand [H2BAS] (20), diphenyltin(IV) complex [Ph2Sn(BAS)] (23) was the most toxic with LC50 values of 15.31 μg/mL. The evaluation of antibacterial activities of ligand [H3PAB] (1) and its organotin(IV) complexes (3-8) showed that the complexes (3-8) are more active than the free hydrazone ligand [H3PAB] (1).